Is There Really Relationship between Androgenetic Alopecia and Metabolic Syndrome? - Seyran Ozbas Gok; Asli Akin Belli; Emine Dervis (Dermatology Research and Practice)
Background. There are several studies investigating the relationship between androgenetic alopecia (AGA) and metabolic syndrome (MS) with conflicting results. Objective. We sought to investigate whether there is a relationship between AGA and MS. Methods. A case-control study including 74 male patients with AGA and 42 male controls was conducted. Age, duration of AGA, AGA onset age, anthropometric measures, body mass index, lipid parameters, fasting blood glucose, blood pressure, and presence of MS were recorded. Results. Of the 74 male AGA patients (age range 20–50 years, mean 32.14), 24 were in stage 2, 26 were in stage 3, 17 were in stage 3V, 1 was in stage 5, and 6 were in stage 7. There was no significant difference in the rate of MS between AGA and control groups (P=0.135). Among the evaluated parameters, only systolic blood pressure in AGA group was significantly higher than control group. Conclusion. In contrast to the most of the previous studies, our study does not support the link between AGA and MS. To exclude confounding factors such as advanced age and therefore metabolic disturbances, further studies are needed with large group of AGA patients including different age groups and varying severity.